Structural analysis of the Zipaquira Anticline (Eastern Cordillera, Colombia) (2016)
We report geological mapping, recollection of kinematic data, fracture data and transverse sections along the Zipaquira Anticline (ZA) used to recognize the deformation mechanisms involved in the kinematic evolution of the ZA. The Zipaquira Anticline (ZA) is an assimetrical fold with variation in the strike of fold axis and affected by some transverse faults (Transverse Zones) along its extension. The main fracture set in the ZA was formed in a prefolding stage (J1), controlling the formation and propagation of sin-folding fractures (J2). Another fracture set (J3) was only recognized near the Zipaquira Lineament where several factors converge to deform considerably the rocks (e.g. Salt diapirs). We calculate the stress tensor from kinematic data, resulting in fractures formed in an extensional environment induced by diapir intrusion in the fold core. According to the transverse sections and previous considerations, thickness variation in Upper Cretaceous-Paleocene formations may indicate the onset of the pre-Andean Orogeny and the uplift of separated blocks, controlled by the transverse zones.